IMPLEMENTASI RME UNTUK KEMAMPUAN BERPIKIR KOMPUTASIONAL MATEMATIS BERDASARKAN KEMANDIRIAN BELAJAR SISWA - Nabila, Sabika Atha; Fatra, Maifalinda; Diwidian, Femmy (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
The low mathematical computational thinking ability of students is caused by the lack of mathematics learning innovation that supports this ability. This study aims to analyse the effect of Realistic Mathematics Education on mathematical computational thinking ability based on students self-regulated learning. The research design used was a pseudo-experiment with a 2x3 factorial design. This research was conducted in class XI of one of South Tangerang State High School. The sample consisted of 42 students in each experimental and control class in which there were high, medium, low self-regulated learning groups. Data were collected using tests and questionnaires that had been tested for validity and reliability. Data were analysed using two-way analysis of variance. The test results showed that: 1) there is a significant average difference in mathematical computational thinking ability between students learning using Realistic Mathematics Education and students learning using conventional approaches, 2) there is a significant average difference in mathematical computational thinking ability between students who have high, medium, and low self-regulated learning, and 3) there is no interaction between learning approaches on mathematical computational thinking ability in terms of students self-regulated learning